2019
DOI: 10.1371/journal.pntd.0007493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for detection of asymptomatic individuals infected with Leishmania infantum in the state of Piauí, Brazil

Abstract: Background Visceral Leishmaniasis in humans presents with fever, anemia, and splenomegaly and can be lethal if not treated. Nevertheless, the majority of Leishmania infantum -infected individuals does not manifest symptoms and remain so provided they are not immunosuppressed. In this work, the performance of different tests was evaluated to detect asymptomatic individuals who were living in Teresina, Piauí state, Brazil, an endemic area for VL. Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…However, no VL case was positive on the IgM test, and one patient diagnosed with Mycobacterium infection was IgM positive [ 39 ], disclosing, therefore, the sensitivity and specificity of anti- Leishmania IgM antibodies for VL diagnosis. In 2019, Porcino et al [ 42 ] also evaluated the ICT Kalazar Detect and Onsite Leishmania IgG/IgM Combo Rapid Test performance and obtained 76% and 64% sensitivities, respectively, in patients with active VL.…”
Section: Discussionmentioning
confidence: 99%
“…However, no VL case was positive on the IgM test, and one patient diagnosed with Mycobacterium infection was IgM positive [ 39 ], disclosing, therefore, the sensitivity and specificity of anti- Leishmania IgM antibodies for VL diagnosis. In 2019, Porcino et al [ 42 ] also evaluated the ICT Kalazar Detect and Onsite Leishmania IgG/IgM Combo Rapid Test performance and obtained 76% and 64% sensitivities, respectively, in patients with active VL.…”
Section: Discussionmentioning
confidence: 99%
“…The Leishmania-specific whole blood stimulation assay has also been evaluated in different endemic areas of Leishmania spp. for the detection of subjects with asymptomatic infection [36,38,39]. However, specificity problems of the soluble Leishmania antigens used, in particular crossreactivity with similar pathogens like Trypanosoma cruzi and Toxoplasma gondii, could be problematic when targeting a diagnostic or predictive tool in coendemic countries, which may be of lesser concern for its development as a test-of-cure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that the baseline profile of circulating biomarkers presented by the AS group characterizes the asymptomatic infection. Moreover, studies using antigen-stimulated cells have identified and suggested the use of biomarkers, such as CXCL-10 and CXCL9 chemokines (Ibarra-Meneses et al ., 2017; Porcino et al ., 2019) and IL-12, IL-2, IFN- γ , IL-17A, IL-22, IL-4 and IL-10 cytokines (Peruhype-Magalhães et al ., 2005; Pitta et al ., 2009; Romano et al ., 2009; Ibarra-Meneses et al ., 2017) for the detection of L. infantum -infected individuals. These studies clearly show that asymptomatic VL individuals have specific immune response profiles that differ from uninfected individuals living in areas endemic for VL and from patients with active VL.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown basal immunological biomarker levels in asymptomatic VL infections (Peruhype-Magalhães et al ., 2006; Khoshdel et al ., 2009; Costa et al ., 2012). On the other hand, studies using antigen-stimulated cells have identified and suggested the use of biomarkers, such as CXCL-10 and CXCL9 chemokines (Ibarra-Meneses et al ., 2017; Porcino et al ., 2019) and IL-12, IL-2, IFN- γ , IL-17A, IL-22, IL-4, and IL-10 cytokines (Peruhype-Magalhães et al ., 2005; Pitta et al ., 2009; Ibarra-Meneses et al ., 2017), for the detection of L. infantum -infected individuals. These findings corroborate the hypothesis that cell immunity is present and usually persists for several years.…”
Section: Introductionmentioning
confidence: 99%